2020
DOI: 10.3390/ijms21176179
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms Underlying Adult Post Stroke Neurogenesis

Abstract: Stroke remains the leading cause of adult disability. Post-stroke neurogenesis contributes to functional recovery. As an intrinsic neurorestorative process, it is important to elucidate the molecular mechanism underlying stroke-induced neurogenesis and to develop therapies designed specifically to augment neurogenesis. Epigenetic mechanisms include DNA methylation, histone modification and its mediation by microRNAs and long-non-coding RNAs. In this review, we highlight how epigenetic factors including DNA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 138 publications
(163 reference statements)
0
17
0
Order By: Relevance
“…Meanwhile, our results in vivo also suggested that HDAC1 repression is correlated to the reduction of mNSS, edema formation, and cerebral infarction volume. Nevertheless, downstream regulatory mechanisms of miRNAs are currently a widely studied mechanism ( Chen et al, 2020 ; Liu J. et al, 2020 ), and epigenetic mechanisms such as DNA methylation and histone modification are also known to mediate miRNAs, which in turn have a regulatory role on epigenetics ( Chen et al, 2018 ; Liu X. et al, 2020 ; Zhao et al, 2020 ). It remains to be established whether miR-410 can regulate other epigenetic markers in an HIBD model.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our results in vivo also suggested that HDAC1 repression is correlated to the reduction of mNSS, edema formation, and cerebral infarction volume. Nevertheless, downstream regulatory mechanisms of miRNAs are currently a widely studied mechanism ( Chen et al, 2020 ; Liu J. et al, 2020 ), and epigenetic mechanisms such as DNA methylation and histone modification are also known to mediate miRNAs, which in turn have a regulatory role on epigenetics ( Chen et al, 2018 ; Liu X. et al, 2020 ; Zhao et al, 2020 ). It remains to be established whether miR-410 can regulate other epigenetic markers in an HIBD model.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies had shown epigenetic modifications played significant roles in the molecular and cellular mechanisms for brain ischemic stroke ( Miao et al., 2015 ; Liu et al., 2020 ). During the past several years, the NLRP3 inflammasome is a vital regulator for cytokine secretions during ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…118 Research has identified epigenetic changes as both cause and consequence of cerebral ischemia and stroke. 119,120 Therefore it is conceivable that ischemia could lead to altered expression of neurosteroidogenic enzymes and neuroactive steroids.…”
Section: Neuroendocrine Microbiotic and Epigenetic Changes Associated...mentioning
confidence: 99%